Flame-retardant polycarbonate foam and preparation method thereof
The high-temperature saturation-cooling foaming method addresses crystallization issues in polycarbonate foam production, resulting in a high-ratio, flame-retardant foam with enhanced mechanical properties and fire safety for structural and aerospace applications.
Patent Information
- Application Number
- CN202411758819.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
AI Technical Summary
Existing polycarbonate foam materials face challenges in achieving high foaming ratios, uniformity, and fire safety, particularly due to crystallization issues during CO2 foaming, which limits their application in demanding fields like electric vehicles and aerospace.
A high-temperature saturation-cooling foaming method is employed, where a PC/flame retardant blend is saturated at 180-240°C under 5-30 MPa, then quickly cooled to 150-180°C for 5-60 minutes before pressure relief, inhibiting crystallization and enhancing foaming efficiency.
The method produces a flame-retardant polycarbonate foam with a high foaming ratio of up to 20 times, excellent mechanical properties, and improved fire safety, suitable for large-scale production and applications in structural materials and aerospace.
Smart Images

Figure CN119219965A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foaming materials, and in particular to a flame retardant polycarbonate foam and a preparation method thereof. Background Art
[0002] Polymer foam materials have been widely used in aerospace, ships, rail transit, automobiles, wind power generation, cushioning packaging, construction and many other fields, and have become important basic chemical materials that are indispensable to people's production and life. However, the commercialized polymer foam materials have more or less problems such as being unfavorable to environmental protection, poor performance, and low fire safety, and many of them are difficult to meet the new and developing needs. Among them, with the rapid development of electric vehicle production and use, the battery safety of electric vehicles has attracted widespread attention worldwide. Since battery failure is usually related to mechanical-thermal coupling behavior, there is an urgent need for a multifunctional thermal insulation material that requires low density (lightweight), high mechanical strength (to prevent mechanical impact), high heat resistance, low thermal conductivity (to avoid thermal runaway), and high fire safety. At present, the development of new, environmentally friendly, and high-performance polymer foam materials has become an important development direction of polymer material processing and molding.
[0003] Polycarbonate (PC) is one of the five major engineering plastics. The most widely used in commercial applications is bisphenol A polycarbonate, namely BPA-polycarbonate (hereinafter referred to as polycarbonate). It has excellent comprehensive performance, balanced mechanical properties, good dimensional stability, easy coloring, excellent aging resistance and electrical insulation properties. In addition, compared with ordinary thermoplastic resins, polycarbonate itself has better flame retardant properties, vertical combustion can reach UL-94 V-2 level, and the limiting oxygen index (LOI) can reach 26-28%; after adding a certain amount of flame retardant, polycarbonate materials with good flame retardant properties can be obtained. Therefore, polycarbonate materials are widely used in electronics, electrical appliances, aerospace, machinery, automobiles, textiles, light industry and construction industries; polycarbonate can be used as one of the bases for preparing new, high-performance, high-fire safety foam materials.
[0004] However, since the PC molecular chain has good symmetry and regularity, during sc-CO2 foaming, the plasticizing effect of CO2 improves the mobility of the PC molecular chain, resulting in rearrangement and crystallization of the PC molecular chain. After the addition of additives, the additives further accelerate the nucleation and crystallization of PC as nucleation sites, which makes the PC foaming performance worse and even difficult to foam. In order to avoid the influence of crystallization in the preparation of polycarbonate foam, the applicant team has previously developed a method for preparing polycarbonate foam materials. The specific method is to foam the polycarbonate raw material in a closed container under the conditions of a physical foaming agent and 5~60MPa (see Chinese patent document with publication number CN 116690882 A). This technology mainly uses the method of in-mold molding to prepare polycarbonate bead molding foam. The in-mold molding of this method not only effectively avoids the limitation of crystallization on foaming performance, but also can be molded in one step, but the density of the prepared foam material is high and the foam uniformity needs to be further improved. Summary of the invention
[0005] In view of this, the present invention provides a flame retardant polycarbonate foam and a preparation method thereof. The polycarbonate foam material provided by the present invention has the characteristics of light weight, good foam uniformity, high flame retardancy, etc., and is convenient for application.
[0006] The present invention provides a method for preparing a flame retardant polycarbonate foam, comprising the following steps:
[0007] The PC raw material and the optional flame retardant are melt-mixed to obtain a PC / flame retardant blend, and processed into a PC / flame retardant blend sheet;
[0008] The PC / flame retardant blend sheet is saturated under physical foaming agent and high temperature conditions, wherein the temperature of the high temperature condition is 180-240° C., and the saturation pressure is 5-30 MPa. After saturation, the temperature is lowered to 150-180° C., and the temperature is balanced for 5-60 minutes. After the temperature is balanced, pressure relief foaming is performed, and the foaming ratio of the pressure relief foaming is more than 4 times, so as to obtain a flame-retardant polycarbonate foam.
[0009] In an embodiment of the present invention, the PC raw material is one or more of aliphatic polycarbonate, aromatic polycarbonate and aliphatic-aromatic polycarbonate.
[0010] In an embodiment of the present invention, the flame retardant is one or more of a silicon-based flame retardant, a boron-based flame retardant, a sulfonate-based flame retardant, a phosphorus-based flame retardant, a metal hydroxide flame retardant, an expanded graphite flame retardant and a carbon nanotube flame retardant, preferably a silicon-based flame retardant or a sulfonate-based flame retardant.
[0011] In an embodiment of the present invention, the mass of the flame retardant is within 30% of the mass of the PC raw material, preferably 1-20%, and more preferably 2-10%.
[0012] In an embodiment of the present invention, the PC / flame retardant blend further comprises a polytetrafluoroethylene anti-drip agent.
[0013] In an embodiment of the present invention, the temperature of the melt mixing is 200-300° C., preferably 240-280° C., and the PC / flame retardant blend sheet with a thickness of less than 20 mm is formed by flat plate hot pressing or sheet extrusion.
[0014] In an embodiment of the present invention, the physical foaming agent is nitrogen and / or carbon dioxide, preferably carbon dioxide.
[0015] In an embodiment of the present invention, the temperature of the high temperature condition is 180~240°C, preferably 200~220°C, the saturated pressure is 6~15MPa, preferably 8~12MPa, and the saturated time is 60~300min, preferably 70~180min, and more preferably 90~150min.
[0016] In an embodiment of the present invention, the cooling temperature is reduced to 150-180° C., preferably 155-165° C., and the temperature is balanced for 5-60 minutes, preferably 10-30 minutes.
[0017] The present invention provides a flame retardant polycarbonate foam, which is obtained by the preparation method described above and has a limiting oxygen index of more than 24.8, preferably more than 26-27.
[0018] Based on the characteristics that polycarbonate is difficult to effectively form crystals at high temperatures, the present invention proposes a one-pot method of high-temperature saturation-cooling foaming to prepare flame-retardant polycarbonate composite foam. The method can first process to form a PC / flame retardant blend sheet, and then by saturating at a specific high temperature, the formation of polycarbonate crystals during the saturation process can be inhibited, and the physical foaming agent has a faster diffusion rate at high temperature, which can shorten the saturation time. After saturation, the temperature is quickly cooled to a temperature suitable for foaming for foaming, thereby preparing a flame-retardant polycarbonate composite foam material with a high foaming ratio (up to 20 times) and excellent performance. The preparation method of the flame-retardant polycarbonate (PC) foam material of the present invention avoids the crystallization of PC induced by plasticization during the CO2 saturation process in the existing method for preparing polycarbonate foam, and at the same time shortens the saturation time by utilizing the faster diffusion rate of the physical foaming agent under high temperature conditions, thereby improving production efficiency. The method is simple in process, high in efficiency, green and environmentally friendly, and is conducive to large-scale production and processing. The flame-retardant polycarbonate (PC) foam material of the present invention has the advantages of temperature resistance, high flame retardancy, good mechanical properties, etc., and has broad application prospects in structural materials, automobiles, aerospace, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 This is a photo of a foam sample saturated with foam at 165°C in Comparative Example 1 of the present invention;
[0021] Figure 2 This is a photo of a foam sample prepared by cooling the temperature from 180°C to 165°C for foaming in Example 1 of the present invention;
[0022] Figure 3 This is a scanning electron microscope image of the cell structure of the foam sample of Example 1 of the present invention;
[0023] Figure 4 This is a photo of a foam sample formed by in-mold foaming in Comparative Example 2 of the present invention;
[0024] Figure 5 A schematic diagram of the structural formula of the self-made polyborosiloxane as a flame retardant used in Examples 3, 6 and 10 of the present invention;
[0025] Figure 6 This is a scanning electron microscope image of the cell structure of the PC / polyborosiloxane composite foam of Example 3 of the present invention. DETAILED DESCRIPTION
[0026] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the technical scheme of the present invention is now described in detail below in conjunction with specific embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0027] The present invention provides a method for preparing a flame retardant polycarbonate foam, comprising the following steps:
[0028] The PC raw material and the optional flame retardant are melt-mixed to obtain a PC / flame retardant blend, and processed into a PC / flame retardant blend sheet;
[0029] The PC / flame retardant blend sheet is saturated under physical foaming agent and high temperature conditions, wherein the temperature of the high temperature condition is 180-240° C., and the saturation pressure is 5-30 MPa. After saturation, the temperature is lowered to 150-180° C., and the temperature is balanced for 5-60 minutes. After the temperature is balanced, pressure relief foaming is performed, and the foaming ratio of the pressure relief foaming is more than 4 times, so as to obtain a flame-retardant polycarbonate foam.
[0030] The polycarbonate foam provided by the invention has the characteristics of light weight, good foam uniformity, high flame retardancy, etc., and is easy to prepare, highly efficient, green and environmentally friendly, and is conducive to large-scale production and processing.
[0031] In the present invention, the dried PC raw materials are preferably weighed according to the composition and weight, and melt-blended at 200-300° C. (depending on the type and amount of the flame retardant added) to form a PC / flame retardant composite sheet.
[0032] Wherein, the PC raw material can be a mixture of one or more of aliphatic polycarbonate, aromatic polycarbonate and aliphatic-aromatic polycarbonate, which is the matrix of polycarbonate foam material. The key parameters of the PC raw material include: melt index 1~10 g / 10min (standard method conditions), preferably 2~5 g / 10min. Some embodiments may not use flame retardants, and the prepared pure PC foam has a higher foaming ratio. Some embodiments use flame retardants, and the flame retardants can be inorganic or organic, including one or more of silicon flame retardants, boron flame retardants, sulfonate flame retardants, phosphorus flame retardants, metal hydroxide flame retardants, expanded graphite flame retardants and carbon nanotube flame retardants, preferably silicon flame retardants or sulfonate flame retardants. The silicon-based flame retardant includes silicon dioxide, silicate, silane polymer, etc., and the sulfonate-based flame retardant includes one or more of potassium perfluorobutyl sulfonate, sodium dodecylbenzene sulfonate, sodium 2,4,5-trichlorobenzene sulfonate, and potassium benzenesulfonylbenzene sulfonate. The metal hydroxide flame retardant is such as magnesium hydroxide and aluminum hydroxide; the boron-based flame retardant is selected from one or more of borax, boric acid, zinc borate, calcium metaborate, ammonium metaborate, ammonium pentaborate, sodium metaborate, ammonium fluoroborate and zinc fluoroborate, etc.; the phosphorus-based flame retardant is mainly an aromatic phosphate flame retardant, such as 4,4-dihydroxybiphenyl bis (diphenyl phosphate); the phosphazene flame retardant includes but is not limited to hexaphenoxy cyclotriphosphazene.
[0033] In some embodiments of the present invention, the mass of the flame retardant is within 30% of the mass of the PC raw material, preferably 1-20%, and more preferably 2-10%. In addition, the PC / flame retardant blend also contains a polytetrafluoroethylene (PTFE) anti-drip agent, which can be added in an amount of 0.1-2% of the mass of the PC raw material, preferably 0.2-0.5%. When PTFE is used as an anti-drip agent, its molecular weight is about 4 to 5 million; after being subjected to the shear force of the rotating screw, this high molecular weight polytetrafluoroethylene is fibrillated to form a mesh structure to prevent dripping.
[0034] After the PC raw material and the flame retardant described in the embodiment of the present invention are melt-mixed, a PC / flame retardant blend can be obtained. The melt mixing process is also called melt blending, which can be melt mixing in an internal mixer or melt mixing in an extruder. The processing into a PC / flame retardant blend sheet described in the embodiment of the present invention is the process of making a sheet, which can be hot-pressed into a sheet by a flat vulcanizer or processed into a sheet by a sheet extrusion device. The melt blending and processing of materials such as PC into sheets are operating methods well known to technicians in the industry, wherein the temperature of the melt mixing can be 200~300℃, preferably 240~280℃, and the PC / flame retardant blend sheet (or composite sheet, etc.) with a thickness of less than 20mm is formed by flat hot pressing or sheet extrusion, and the thickness is further 3~12mm, such as 5~10mm.
[0035] In the embodiment of the present invention, the PC / flame retardant blend sheet obtained in the above steps is placed in a foaming kettle, added to a mold with a compressible cavity, and the mold is fixed by a flat hot press. At 180-240°C (depending on the type and amount of flame retardant added), a physical foaming agent such as carbon dioxide is preferably introduced to increase the pressure to 5-15MPa, and saturated for 60-300 minutes to achieve CO2 saturation in the mixture sheet to reach equilibrium.
[0036] In an embodiment of the present invention, the physical foaming agent is nitrogen and / or carbon dioxide (CO2), preferably carbon dioxide. The embodiment of the present invention is saturated at a certain high temperature (at which PC is difficult to effectively crystallize). The saturation at this high temperature inhibits the formation of polycarbonate crystals during the saturation process, which can prevent the problem of crystallization-limited foaming of PC in CO2. The faster diffusion rate of supercritical CO2 at high temperature can also be used to shorten the saturation time. The temperature of the high temperature condition is preferably 200~220℃, the saturated pressure (passing physical foaming agent to boost saturation) is preferably 6~15MPa, more preferably 8~12MPa, and the time can be 60~300min, preferably 90~150min, etc.
[0037] After saturation equilibrium, the embodiment of the present invention can use the cooling system to quickly reduce the mold temperature to the foaming temperature (such as 150-180°C), and then perform temperature equilibrium (such as heat preservation for 5-60 minutes); after the temperature equilibrium is stable, pressure relief foaming is performed to obtain a PC / flame retardant composite foam material with a certain foaming ratio (which can be referred to as flame retardant polycarbonate foam, etc.). The rate of rapid temperature reduction can be 10-30°C / min; and the time of pressure relief foaming can be 0.5-2s.
[0038] In an embodiment of the present invention, the cooling temperature can be reduced to 150-180°C, preferably 155-165°C, and the temperature balance is 5-60 minutes, preferably 10-30 minutes; the foaming ratio of the pressure relief foaming is more than 4 times, and can reach 20 times. The foaming ratio is the expansion ratio, which is defined as the ratio of the foam volume after expansion to the original material volume (which can be understood as the ratio of the original material density to the foam density. The higher the foaming ratio, the lower the foam density). In other words, the higher the foaming ratio, that is, the greater the ratio of the original material density to the foam density, the smaller the foam density, the lighter it is, the lower the thermal conductivity, the better the thermal insulation performance, etc.
[0039] Compared with the conventional foaming method in which saturation and foaming are performed at the same temperature, the high-temperature saturation-cooling foaming method under certain conditions is adopted in the embodiment of the present invention, which can well solve the problem of PC crystallization in the foaming process and obtain a low-density PC flame-retardant foam with a smooth surface.
[0040] The present invention provides a flame retardant polycarbonate foam, which is obtained by the preparation method described above and has a limiting oxygen index of more than 24.8, preferably more than 26-27.
[0041] The flame retardant polycarbonate foam provided by the embodiment of the present invention has uniform overall shape, good morphology, and high foaming ratio. In addition, the flame retardant polycarbonate foam has better mechanical properties and good flame retardant properties, which is conducive to application in the fields of structural materials, automobiles, aerospace, etc.
[0042] In order to better illustrate the present invention, the following examples are further illustrated. In the examples, all raw reagents and materials are commercially available, and the experimental methods without specific experimental conditions are conventional methods and conditions well known in the art.
[0043] Comparative Example 1
[0044] The purchased PC (Covestro, aromatic polycarbonate 2805, melt index: 10) and 0.3wt% sodium dodecylbenzene sulfonate (Shanghai Aladdin Biochemical Technology Co., Ltd.) were melt-mixed at 240°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for foaming. The foaming temperature was 165°C, the foaming pressure was 10MPa, the saturation time was 180min, and the sample was taken out after the pressure was released to obtain a PC foam material.
[0045] The optical photograph of the foam is shown in Figure 1 As shown. It was observed that cracks appeared on the outside of the foam. This is mainly because the plasticization effect of CO2 at this temperature makes PC easy to crystallize, and as CO2 diffuses from the outside to the inside, the outer layer crystallizes first while the inner layer crystallizes less, resulting in expansion and cracking of the outer layer.
[0046] Example 1
[0047] The purchased PC (Covestro, aromatic polycarbonate 2805, melt index: 10) and 0.3wt% sodium dodecylbenzene sulfonate (Shanghai Aladdin Biochemical Technology Co., Ltd.) were melt-mixed at 240°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 180°C, and CO2 was introduced at a saturation pressure of 10MPa for 180min. After saturation, the temperature of the foaming kettle was rapidly reduced (cooling rate of 20-25°C / min, the same as in the following examples) to a foaming temperature of 165°C, and then the temperature was balanced for 20min, and a flame-retardant PC foam material was obtained by a 0.5-2s pressure relief operation.
[0048] The optical photograph of the foam is shown in Figure 2 As shown; the cell structure of the foam material is as Figure 3 As shown, Figure 3This is a scanning electron microscope image of a foam material sample. After testing, the sample has a uniform overall shape and a good morphology; its foaming ratio can reach 12 times, the limiting oxygen index is 28.0±0.2, and the UL-94 is V-2 grade.
[0049] Compared with the conventional foaming method of Comparative Example 1 (saturation and foaming at the same temperature), the high-temperature saturation (180°C) - cooling foaming (160°C) method adopted in this embodiment well solves the problem of PC crystallization in the foaming process and obtains a low-density PC flame-retardant foam with a smooth surface.
[0050] Comparative Example 2
[0051] According to the previous in-mold foaming method of the applicant team (see the Chinese patent document with publication number CN 116690882 A), the purchased PC particles (Covestro, aromatic polycarbonate 2805, melt index: 10, filling amount is 12% of the volume of the closed container, and the designed expansion ratio is 10 times) were simply mixed with 0.5wt% of sodium dodecylbenzene sulfonate (Shanghai Aladdin Biochemical Technology Co., Ltd.) and placed in a rectangular mold, and then placed in a foaming kettle for foaming. The foaming temperature is 167°C, the foaming pressure is 10MPa, and the saturation time is 1h. After the pressure is released, the foam sample is immediately cooled together with the mold to obtain a flame-retardant PC foam material. Upon observation, the sample presents an irregular shape. The expanded foam cannot fill the entire closed container because the actual expansion ratio is less than the designed expansion ratio, and a complete foam cannot be obtained. This method is difficult to prepare PC composite foam with a high foaming ratio. The optical photograph of the foam is as follows Figure 4 shown.
[0052] Example 2
[0053] The purchased PC particles (Covestro, aromatic polycarbonate 2805, melt index: 10) and 0.5wt% sodium dodecylbenzene sulfonate (Shanghai Aladdin Biochemical Technology Co., Ltd.) were melt-mixed at 240°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 200°C, a saturation pressure of 10MPa, and a saturation time of 60min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 167°C, and then the temperature was balanced for 20min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0054] After testing, the foam sample has a uniform overall shape and good morphology; its foaming ratio is 17.6 times, the limiting oxygen index is 27.8±0.2, and the UL-94 is V-2. Compared with the limited foaming of the in-mold foaming method in Comparative Example 2, which makes it difficult to prepare PC foam with a high foaming ratio, the high-temperature saturation-cooling foaming used in this embodiment has no restriction on foam growth during the foaming process, so that a high-ratio (17.6 times) PC foam can be obtained.
[0055] Comparative Example 3
[0056] The purchased PC (Chimei Industrial, aromatic polycarbonate 110-L, melt index: 10) and 2wt% polyborosiloxane (self-made, the structure is shown in the figure) were mixed. Figure 5 As shown, molecular weight: 2000-500000, the same as in the following examples), the blend was processed into a 5 mm plate after melt mixing at 240°C, and then placed in a foaming kettle for foaming, the foaming temperature was 160°C, the foaming pressure was 10MPa, the saturation time was 180min, and the sample was taken out after pressure relief to obtain a PC foam material. It was observed that the mixed plate was almost not foamed, which was because the heterogeneous nucleation of polysiloxane promoted the crystallization of PC, making it difficult for the mixture to expand.
[0057] Example 3
[0058] The purchased PC particles (Chimei Industrial, aromatic polycarbonate 110-L, melt index: 10) and 2wt% polyborosiloxane (self-made) were melt-mixed at 240°C and processed into a 5 mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 200°C, a saturation pressure of 10MPa, and a saturation time of 180min. After saturation, the temperature of the foaming kettle was quickly reduced to the foaming temperature of 160°C, and then the temperature was balanced for 30min, and the pressure was released to obtain a flame-retardant PC foam material. The pore structure of this foam is as follows: Figure 6 shown.
[0059] After testing, the foam sample has a uniform overall shape and intact morphology; its foaming ratio can reach 11 times, the limiting oxygen index is 26.1±0.2, and the UL-94 is V-2 grade. In Comparative Example 3, the heterogeneous nucleation of the added polyborosiloxane accelerated the crystallization, so that crystals were quickly formed during the conventional foaming process, resulting in failure to foam. Compared with Comparative Example 3, the high-temperature saturation-cooling foaming method used in Example 3 can still well inhibit the formation of PC crystals after adding polyborosiloxane, and a high-ratio (11 times) PC / polyborosiloxane composite flame-retardant foam is obtained.
[0060] Comparative Example 4
[0061] The purchased PC (Covestro, aromatic polycarbonate 3106, melt index: 6) and 1wt% expanded graphite (Qingdao Yanhai Carbon Materials Co., Ltd.) were melt mixed at 220°C and processed into a 5mm thick plate. Then, according to the method of Zhai et al. (Polymer. 2006, 47, 7580-7589), the saturation was carried out at 50°C and 12MPa for 20h, and then the sample was placed in 165°C glycerol for foaming for 30s, and finally the sample was taken out and cooled. After testing, the sample of this method was almost not foamed, and the volume expansion ratio was only 1.3 times.
[0062] Example 4
[0063] The purchased PC particles (Covestro, aromatic polycarbonate 3106, melt index: 6) and 1wt% expanded graphite (Qingdao Yanhai Carbon Materials Co., Ltd.) were melt-mixed at 220°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 240°C, a saturation pressure of 15MPa, and a saturation time of 60min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 165°C, and then the temperature was balanced for 40min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0064] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio can reach 12.0 times, the limiting oxygen index is 27.0±0.2, and the UL-94 is V-2 grade. Compared with the low-temperature saturation in Comparative Example 4, the saturation efficiency is low due to the long time (20h) required for the diffusion rate to reach the full saturation rate, and the saturation efficiency is improved by shortening the saturation time (1h) at high temperature because the diffusion of CO2 is greatly accelerated at high temperature.
[0065] Example 5
[0066] The purchased PC particles (Mitsubishi, aromatic polycarbonate E2000UR, melt index: 5.3) were melt-processed at 280°C, then processed into 5 mm thick plates, and then put into a foaming kettle for saturation. The saturation temperature was 220°C, the saturation pressure was 12 MPa, and the saturation time was 60 min. After saturation, the temperature of the foaming kettle was quickly reduced to the foaming temperature of 165°C, and then the temperature was balanced for 60 min, and the pressure was released to obtain pure PC foam material.
[0067] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 12.0 times, and the limiting oxygen index is 24.8±0.2.
[0068] Example 6
[0069] The purchased PC particles (Mitsubishi, aromatic polycarbonate E2000UR, melt index: 5.3) and 10wt% polyborosiloxane (self-made) were melt-mixed at 240°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 220°C, a saturation pressure of 13MPa, and a saturation time of 60min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 165°C, and then the temperature was balanced for 5min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0070] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 20 times, the oxygen index is 30.1±0.2, and the UL-94 is V-0 grade.
[0071] Example 7
[0072] The purchased PC particles (Mitsubishi, aromatic polycarbonate M7027BF, melt index: 2.3) and 20 wt% polyphenylphosphonate diphenyl sulfone (Hubei Xingyan New Materials Co., Ltd.) were melt-mixed at 210°C and processed into a 5 mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 180°C, a saturation pressure of 5 MPa, and a saturation time of 120 min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 150°C, and then the temperature was balanced for 10 min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0073] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 10.0 times, the oxygen index is 30.1±0.2, and the UL-94 is V-0 grade.
[0074] Example 8
[0075] The purchased PC particles (Mitsubishi, aromatic polycarbonate M7027BF, melt index: 2.3) were mixed with 0.5wt% potassium diphenylsulfone sulfonate (Shanghai Jieshikai Biotechnology Co., Ltd.) and 1wt% polytetrafluoroethylene powder (Daikin Industries, Ltd., Japan) at 260°C, and the blend was processed into a 5mm thick plate, and then placed in a foaming kettle for saturation, with a saturation temperature of 200°C, a saturation pressure of 12MPa, and a saturation time of 120min. After saturation, the temperature of the foaming kettle was quickly reduced to the foaming temperature of 180°C, and then the temperature was balanced for 20min, and the pressure was released to obtain a flame-retardant PC foam material.
[0076] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 4.3 times, the oxygen index is 32.0±0.2, and the UL-94 is V-0 grade.
[0077] Example 9
[0078] The purchased PC particles (Dalian Ruifeng Chemical Co., Ltd., aliphatic polycarbonate RU-71-035, melt index: 5) and 7wt% sodium metaborate (Wuhan Kemik Biomedical Technology Co., Ltd.) were melt mixed at 260°C and processed into a 5mm thick plate, and then placed in a foaming kettle for saturation, with a saturation temperature of 190°C, a saturation pressure of 8MPa, and a saturation time of 90min. After saturation, the temperature of the foaming kettle was quickly reduced to the foaming temperature of 170°C, and then the temperature was balanced for 25min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0079] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 4.3 times, the oxygen index is 28.0±0.2, and the UL-94 is V-2 grade.
[0080] Example 10
[0081] The homemade PC (aliphatic-aromatic polycarbonate, structure as shown below, molecular weight: 5000-200000) and 15wt% polysiloxane (homemade) were melt-mixed at 220°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 200°C, a saturation pressure of 11MPa, and a saturation time of 100min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 160°C, and then the temperature was balanced for 30min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0082] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 15 times, the oxygen index is 29.0±0.2, and the UL-94 is V-0 grade.
[0083] The repeating units of the aliphatic-aromatic polycarbonate shown include structures such as diphenylmethane;
[0084] .
[0085] Embodiment 11
[0086] The purchased PC particles (Covestro, aromatic polycarbonate APEC, melt index: 0.7) and 30wt% aluminum hydroxide (Jiangxi Tuoan New Materials Co., Ltd.) were melt-mixed at 280°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 200°C, a saturation pressure of 13MPa, and a saturation time of 90min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 175°C, and then the temperature was balanced for 30min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0087] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 5.4 times, the oxygen index is 28.0±0.2, and the UL-94 is V-1 grade.
[0088] Example 12
[0089] The purchased PC particles (Mitsubishi, aromatic polycarbonate M7027BF, melt index: 2.3) and 25wt% magnesium hydroxide (Jiangxi Tuoan New Materials Co., Ltd.) were melt-mixed at 300°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 200°C, a saturation pressure of 13MPa, and a saturation time of 90min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 175°C, and then the temperature was balanced for 30min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0090] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 5.4 times, the oxygen index is 28.0±0.2, and the UL-94 is V-1 grade.
[0091] Example 13
[0092] The purchased PC particles (Mitsubishi, aromatic polycarbonate M7027BF, melt index: 2.3) and 10wt% of hexaphenoxy cyclotriphosphazene (Wuhan Haishan Technology Co., Ltd.) were melt-mixed at 240°C and processed into a 5mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 210°C, a saturation pressure of 12MPa, and a saturation time of 80min. After saturation, the temperature of the foaming kettle was quickly reduced to a foaming temperature of 155°C, and then the temperature was balanced for 40min, and a pressure relief operation was performed to obtain a flame-retardant PC foam material.
[0093] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 8.7 times, the oxygen index is 29.0±0.2, and the UL-94 is V-1 grade.
[0094] Embodiment 14
[0095] The purchased PC particles (Mitsubishi, aromatic polycarbonate M7027BF, melt index: 2.3) and 15wt% bisphenol A bis (diphenyl phosphate) (Jiangxi Tuoan New Materials Co., Ltd.) were melt mixed at 200°C and processed into a 5mm thick plate, and then placed in a foaming kettle for saturation, with a saturation temperature of 200°C, a saturation pressure of 10MPa, and a saturation time of 90min. After saturation, the temperature of the foaming kettle was quickly reduced to the foaming temperature of 160°C, and then the temperature was balanced for 15min, and the pressure was released to obtain a flame-retardant PC foam material.
[0096] After testing, the overall shape of the sample is uniform, the morphology is intact, the foaming ratio is 6.4 times, the oxygen index is 28.0±0.2, and the UL-94 is V-2 grade.
[0097] Embodiment 15
[0098] The purchased PC (Covestro, aromatic polycarbonate 2805, melt index: 10) and 0.3wt% sodium dodecylbenzene sulfonate (Shanghai Aladdin Biochemical Technology Co., Ltd.) were melt mixed at 240°C and processed into a 20mm thick plate, which was then placed in a foaming kettle for saturation at a saturation temperature of 200°C, and CO2 was introduced at a saturation pressure of 30MPa for 300min. After saturation, the temperature of the foaming kettle was rapidly reduced (cooling rate 20~25°C / min) to a foaming temperature of 165°C, and then the temperature was balanced for 20min, and a flame-retardant PC foam material was obtained by a 0.5~2s pressure relief operation.
[0099] After testing, the overall shape of the sample is uniform and the morphology is intact; its foaming ratio can reach 10 times, the limiting oxygen index is 28.5±0.2, and the UL-94 is V-2 grade.
[0100] It can be seen from the above embodiments that in the preparation method of the flame-retardant polycarbonate (PC) foam material of the present invention, the faster diffusion rate of the physical foaming agent under high temperature conditions can be used to shorten the saturation time and improve the production efficiency; after saturation, the temperature is lowered to 150-180°C, and the temperature is balanced for 5-60 minutes; after the temperature is balanced, the pressure is released and foamed. The method is simple in process, high in efficiency, green and environmentally friendly, and is conducive to large-scale production and processing. The PC foam material of the embodiment of the present invention has a high foaming ratio, and has the advantages of heat resistance, high flame retardancy, good mechanical properties, etc., and has broad application prospects in structural materials, automobiles, aerospace, etc.
[0101] The above examples are only used to illustrate the technical features and implementation process of the present invention, rather than to limit the technical solution of the present invention. It should be pointed out that for ordinary technicians in this field, the present invention can still be modified or replaced by equivalents, and modifications or replacements that do not deviate from the principles of the present invention are all covered by the protection of the present invention.
Claims
1. A method for preparing a flame retardant polycarbonate foam, characterized in that: The following steps are involved: The PC raw material and the optional flame retardant are melt-mixed to obtain a PC / flame retardant blend, and processed into a PC / flame retardant blend sheet; The PC / flame retardant blend sheet is saturated under physical foaming agent and high temperature conditions, wherein the temperature of the high temperature condition is 180-240° C., and the saturation pressure is 5-30 MPa. After saturation, the temperature is lowered to 150-180° C., and the temperature is balanced for 5-60 minutes. After the temperature is balanced, pressure relief foaming is performed, and the foaming ratio of the pressure relief foaming is more than 4 times, so as to obtain a flame-retardant polycarbonate foam.
2. The preparation method according to claim 1, characterized in that: The PC raw material is one or more of aliphatic polycarbonate, aromatic polycarbonate and aliphatic-aromatic polycarbonate.
3. The preparation method according to claim 1, characterized in that: The flame retardant is one or more of a silicon flame retardant, a boron flame retardant, a sulfonate flame retardant, a phosphorus flame retardant, a metal hydroxide flame retardant, an expanded graphite flame retardant and a carbon nanotube flame retardant.
4. The preparation method according to claim 1, characterized in that: The mass of the flame retardant is within 30% of the mass of the PC raw material.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The PC / flame retardant blend also contains a polytetrafluoroethylene anti-drip agent.
6. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the melt mixing is 200-300° C., and the PC / flame retardant blend sheet with a thickness of less than 20 mm is formed by flat plate hot pressing or sheet extrusion.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The physical blowing agent is nitrogen and / or carbon dioxide.
8. The preparation method according to claim 7, characterized in that: The temperature of the high temperature condition is 200-220° C., the saturated pressure is 6-15 MPa, and the saturated time is 60-300 min.
9. A flame retardant polycarbonate foam, characterized in that: The product is obtained by the preparation method according to any one of claims 1 to 8, and has a limiting oxygen index of above 24.8.
Citation Information
Patent Citations
Preparation method for polycarbonate microcellular foaming material
CN107674233A
Halogen-free flame-retardant PET (Polyethylene Terephthalate) blended foaming material and preparation method thereof
CN115109396A
Preparation method of polycarbonate foam material
CN116690882A